Separation of Biological Molecules using Electrochemically Etched Nanoporous Silicon Membrane - Burham, Norhafizah; Norjihan Tuan Yaakob, Tuan; Azlan Hamzah, Azrul; Yeop Majlis, Burhannuddin (International Journal of Engineering and Technology, 2019)
This paper presents a separating technique of biological molecules and non-biological particles in solution using nanoporous silicon membranes. The simple separation method has been studied by fabricating the porous silicon membrane with Polydimethylsiloxane (PDMS) to produce the filtration system. The testing procedure began with diluted and sonicated indium oxide particles with deionized (DI) water and mixed with a biological solution. In this experiment setup, biological particles used is protein standard, serum albumin and sodium chloride has been filtered out through this filtration system. As a result, the indium oxide particles were trapped on the nanoporous silicon surface. Meanwhile, biology molecules penetrate the nanoporous silicon membrane with particle and molecule sizes up to 15 nm. The filtered-out particles are inspected under Zetasizer Nano SP to count and measure the size of the particles and molecules. According to the inspected result show 98% biological molecules are filtered out from this nanoporous silicon membrane. Due to this simple fabrication process, porous silicon membranes are able to be integrated to the other component to develop the complete bioMEMS and Lab on Chip system in the future.Â